A structural genomics approach to investigate Dystrophin mutations and their impact on the molecular pathways of Duchenne muscular dystrophy - Elasbali, Abdelbaset Mohamed; Anjum, Farah; AlKhamees, Osama A.; Abu Al-Soud, Waleed; Adnan, Mohd; Shamsi, Anas; Hassan, Md. Imtaiyaz (Frontiers in Genetics, 2025)
BackgroundDystrophin is a key protein encoded by the DMD gene, serves as a scaffold linking the cytoskeleton to the extracellular matrix that plays a critical role in muscle contraction, relaxation, and structural integrity. Mutations, particularly single-point amino acid substitutions, can lead to dysfunctional Dystrophin, causing muscular dystrophies, with Duchenne muscular dystrophy (DMD) being the most severe form.ObjectiveThis study aimed to evaluate the effects of 184 single-point amino acid substitutions on the structure and function of Dystrophin using computational approaches.MethodsMany computational tools were used to predict the impact of amino acid substitutions on protein stability, solubility, and function. Pathogenic potential was assessed using disease phenotype predictors and CADD scores, while allele frequency data from gnomAD contextualized mutation prevalence. Additionally, aggregation propensity, frustration analysis, and post-translational modification sites were analyzed for functional disruptions.ResultsOf the 184 substitutions analyzed, 50 were identified as deleterious, with 41 predicted to be pathogenic. Seventeen mutations were localized in the Calponin-homology (CH) 1 domain, a critical functional region of Dystrophin. Six substitutions (N26H, N26K, G47W, D98G, G109A, and G109R) were predicted to decrease protein solubility and were located in minimally frustrated regions, potentially compromising Dystrophin functionality and contributing to DMD pathogenesis.ConclusionThis study provides novel insights into the molecular mechanisms of DMD, highlighting specific mutations that disrupt Dystrophin’s solubility and function. These findings could inform future therapeutic strategies targeting Dystrophin mutations to address DMD pathogenesis.